Cost estimator's reference manual - Stewart, Rodney D.; Wyskida, Richard M. (Wiley series in new dimensions in engineering, 1995)
In today's hypercompetitive global marketplace, accurate cost estimating is crucial to bottom-line results. Nowhere is this more evident than in the design and development of new products and services. Among managing engineers responsible for developing realistic cost estimates for new product designs, the number-one source of information and guidance has been the Cost Estimator's Reference Manual. Comprehensive, authoritative, and practical, the Manual instructs readers in the full range of cost estimating techniques and procedures currently used in the fields of development, testing, manufacturing, production, construction, software, general services, government contracting, engineering services, scientific projects, and proposal preparation. The authors clearly explain how to go about gathering the data essential to preparing a realistic estimate of costs and guide the reader step by step through each procedure.